2003
DOI: 10.1016/s0006-3495(03)74648-7
|View full text |Cite
|
Sign up to set email alerts
|

General Methods for Analysis of Sequential “n-step” Kinetic Mechanisms: Application to Single Turnover Kinetics of Helicase-Catalyzed DNA Unwinding

Abstract: Helicase-catalyzed DNA unwinding is often studied using "all or none" assays that detect only the final product of fully unwound DNA. Even using these assays, quantitative analysis of DNA unwinding time courses for DNA duplexes of different lengths, L, using "n-step" sequential mechanisms, can reveal information about the number of intermediates in the unwinding reaction and the "kinetic step size", m, defined as the average number of basepairs unwound between two successive rate limiting steps in the unwindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
219
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(221 citation statements)
references
References 38 publications
0
219
0
Order By: Relevance
“…2. This model is similar to the one used to analyze the UvrD helicase kinetics (22,39), with some modifications. The stepping model assumes that the helicase separates a particular length L of dsDNA in n steps; thus, the step size s is L͞n.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2. This model is similar to the one used to analyze the UvrD helicase kinetics (22,39), with some modifications. The stepping model assumes that the helicase separates a particular length L of dsDNA in n steps; thus, the step size s is L͞n.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for the decrease in the step size of T7 helicase from Ϸ9 to Ϸ6 bp when the dTTP concentration is decreased from 2 mM to 200 M is not obvious and requires an understanding of the meaning of the kinetic step size. The kinetic step size is defined as the average number of base pairs unwound between two successive rate-limiting steps in the helicase reaction (22,39). If the rate-limiting step of T7 helicase at low and high dTTP is different, then this might be the reason for the dependence of the kinetic step size on dTTP.…”
Section: Resultsmentioning
confidence: 99%
“…True or intrinsic processivity (P Intr ) is determined by the dissociation probability (P d ) of the enzyme from the polymer. It has also been demonstrated that P Intr corresponds to the average number of catalytic acts performed before the dissociation of the enzyme from the polymer (38). P Intr can realize only on an ideal polymer where P d is independent of the position of the enzyme on polymer.…”
Section: Measurement Of Cellulase Processivity; Methodsmentioning
confidence: 99%
“…Experimental data with only two states was fit to the Equation 1 (29,50) to obtain the rate and processivity parameters,…”
Section: Methodsmentioning
confidence: 99%